IOT Based E-Waste Management System - Muntode, Dange Harshada; Muntode, Mohalkar Ganesh; Muntode, Chaudhari Swapnil; Muntode, Prof. Vyavhare V. A. (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Rapid increases in the volume and kinds of hazardous and solid waste brought on by ongoing urbanization, industrialization, and economic expansion are making it increasingly difficult for national and municipal governments to manage garbage in an efficient and sustainable manner. Global waste management market report 2007 estimates that in 2006, the total volume of municipal solid trash created worldwide reached 2.02 billion tones, a 7% yearly growth since 2003. (Per the 2007 Global Waste Management Market Report.). 2. To reduce the risk to patients’ health and safety as well as the public’s and the environment’s, waste handling, transportation, and disposal must be carefully controlled. Waste is most effectively utilized economically when it is separated. There isn’t one in place at the moment for households to separate their dry, wet, and metallic wastes. In order to send waste straight for processing, this paper suggests an Automated Waste Segregator (AWS), a low-cost, user-friendly solution for a household waste segregation system. Its purpose is to separate the garbage into three categories: dry, wet, and metallic waste. The AWS uses capacitive sensors to discern between wet and dry materials, and a parallel resonant impedance sensing mechanism to identify metallic objects.